2019
DOI: 10.1097/qai.0000000000002057
|View full text |Cite
|
Sign up to set email alerts
|

Brief Report: Impact of PrEP Training for Family Planning Providers on HIV Prevention Counseling and Patient Interest in PrEP in Atlanta, Georgia

Abstract: Background: Safety net family planning (FP) clinics provide vital care for women in high HIV-burden areas and may be ideal pre-exposure prophylaxis (PrEP) delivery sites. Yet, many FP providers lack knowledge about PrEP. Setting: Four safety net FP clinics in Atlanta, Georgia. Methods: We provided a 1.5-hour PrEP informational training for 28 providers working in these sites. To assess the training's impact … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 26 publications
2
30
1
Order By: Relevance
“…However, we suggest that all clinics, prior to PrEP implementation, receive a training on the process for conducting the PrEP cascade (i.e., HIV risk assessment, PrEP patient education, assessing patient eligibility for PrEP, PrEP prescription, and PrEP follow-up care) to ensure that clinic staff, providers, and administrators are informed of necessary requirements. We have previously shown that a 1 hour training is able to significantly increase providers’ PrEP knowledge, attitudes, and skills [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, we suggest that all clinics, prior to PrEP implementation, receive a training on the process for conducting the PrEP cascade (i.e., HIV risk assessment, PrEP patient education, assessing patient eligibility for PrEP, PrEP prescription, and PrEP follow-up care) to ensure that clinic staff, providers, and administrators are informed of necessary requirements. We have previously shown that a 1 hour training is able to significantly increase providers’ PrEP knowledge, attitudes, and skills [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, the characteristics of providers and settings, measurement of PrEP knowledge, and covariates selected for adjustment to reduce confounding bias varied across studies. Nevertheless, evidence from intervention studies supports the idea that improving PrEP knowledge can increase PrEP adoption and prescribing among PCPs ( Bunting et al, 2020 , Clement et al, 2018 , Sales et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, the AIDS Education and Training Center’s (AETC) National HIV Curriculum provides self-guided PrEP training modules for continuing education credits that cover basic information about PrEP clinical guidelines, skills for initiating and monitoring, PrEP efficacy and clinical trial evidence, and potential risks and side effects [ 18 ]. Another recent PrEP training program for family planning providers covered information related to HIV epidemiology and prevention, patient risk assessment and referral, and example case scenarios [ 19 ]. Finally, the Training and Technical Assistance Program (T-TAP) in New York City offers several day-long PrEP trainings on various subjects, including the basics of PrEP, best practices in PrEP education and counseling, and financial barriers and benefits navigation for PrEP [ 20 ].…”
Section: Introductionmentioning
confidence: 99%